Resin materials, laminated films and multilayer printed wiring boards

The resin material with polyimide and aliphatic skeleton-containing compounds addresses embeddability, extrusion, curing temperature, adhesion, and dielectric loss issues, enhancing the performance of multilayer printed wiring boards.

JP7607711B2Active Publication Date: 2024-12-27SEKISUI CHEMICAL CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023122240
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-03-28
Filing Date
2023-07-27
Publication Date
2024-12-27
Estimated Expiration
2039-03-27

AI Technical Summary

Technical Problem

Conventional resin materials for multilayer printed wiring boards face issues such as insufficient embeddability into uneven surfaces, excessive extrusion during lamination, high curing temperatures, poor adhesion to copper substrates, high dielectric loss tangent, and inadequate bending stability.

Method used

A resin material comprising a polyimide compound and an aliphatic skeleton-containing compound, such as a maleimide or benzoxazine compound, with specific molecular weights and ratios, along with an inorganic filler and curing accelerators, to improve embeddability, suppress extrusion, lower curing temperature, reduce dielectric loss tangent, enhance adhesion, and increase bending stability.

Benefits of technology

The resin material effectively improves embeddability, suppresses extrusion, lowers curing temperature, reduces dielectric loss tangent, enhances adhesion to metals, and increases bending stability, resulting in improved handling properties and insulation reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007607711000006
    Figure 0007607711000006
  • Figure 0007607711000001
    Figure 0007607711000001
  • Figure 0007607711000002
    Figure 0007607711000002
Patent Text Reader

Abstract

To provide a resin material which 1) enhances embedding properties to an uneven surface, 2) suppresses excess squeeze out from a periphery of a substrate of a resin material during lamination, 3) keeps curing temperature low, 4) reduces dielectric loss tangent of a cured article, 5) enhances adhesiveness with a metal, and 6) can enhance bending stability of the cured article.SOLUTION: The resin material contains a polyimide compound, and at least one of aliphatic skeleton-containing compound of a maleimide compound having an aliphatic skeleton and a benzoxazine compound having the aliphatic skeleton.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin material containing a polyimide compound, and also to a multilayer printed wiring board using the resin material. [Background technology]

[0002] Conventionally, various resin materials have been used to obtain electronic components such as semiconductor devices, laminates, and printed wiring boards. For example, in a multilayer printed wiring board, a resin material is used to form an insulating layer for insulating between internal layers, or to form an insulating layer located on a surface layer. Wiring, which is generally metal, is laminated on the surface of the insulating layer. In addition, a resin film obtained by filming the resin material may be used to form the insulating layer. The resin material and the resin film are used as insulating materials for multilayer printed wiring boards, including build-up films.

[0003] The following Patent Document 1 discloses a resin composition containing a compound having a maleimide group, a divalent group having at least two imide bonds, and a saturated or unsaturated divalent hydrocarbon group. Patent Document 1 also describes that a cured product of this resin composition can be used as an insulating layer for a multilayer printed wiring board or the like.

[0004] The following Patent Document 2 discloses a resin composition containing (A) a polyfunctional epoxy resin (excluding phenoxy resin), (B) a phenol-based curing agent and / or an active ester-based curing agent, (C) a thermoplastic resin, (D) an inorganic filler, and (E) a quaternary phosphonium-based curing accelerator. The (C) thermoplastic resin is a thermoplastic resin selected from a phenoxy resin, a polyvinyl acetal resin, a polyimide, a polyamide-imide resin, a polyethersulfone resin, and a polysulfone resin. The (E) quaternary phosphonium-based curing accelerator is one or more quaternary phosphonium-based curing accelerators selected from tetrabutylphosphonium decanoate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, and butyltriphenylphosphonium thiocyanate. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] WO2016 / 114286A1 [Patent Document 2] JP 2015-145498 A Summary of the Invention [Problem to be solved by the invention]

[0006] When an insulating layer is formed using a conventional resin material as described in Patent Document 1, the resin material may not be able to embed sufficiently into unevenness of the substrate, or the resin material may overflow excessively from the periphery of the substrate during lamination, making it difficult to control the film thickness. Also, when an insulating layer is formed using a conventional resin material as described in Patent Document 2, the dielectric tangent of the insulating layer may not be sufficiently low, or the adhesion between the insulating layer and the copper substrate may not be sufficiently high.

[0007] On the other hand, in conventional resin materials containing only maleimide compounds having an aromatic skeleton, it is difficult to lower the curing temperature (for example, below 200°C) because the Tg of the maleimide compound is high. In addition, when the curing temperature is lowered, sufficient molecular motion is unlikely to occur, which may result in poor curing. In addition, when the curing temperature is lowered, the resin material laminated in the early stages during the manufacture of a multilayer printed wiring board is heated more times and for a longer period of time than the resin material laminated in the later stages, which may change the electrical characteristics and physical properties of the insulating layer.

[0008] Furthermore, with conventional resin materials, the bending stability of the cured product may not be sufficiently high.

[0009] Thus, the current situation is that it is extremely difficult to 1) improve embedding ability into uneven surfaces, 2) prevent excessive protrusion of the resin material from the periphery of the substrate during lamination, 3) keep the curing temperature low, 4) reduce the dielectric tangent of the cured product, 5) improve adhesion to metals, and 6) improve the bending stability of the cured product. In other words, the current situation is that it is extremely difficult to obtain a resin material that exhibits all of the above effects 1)-6).

[0010] The object of the present invention is to provide a resin material that can 1) improve embedding properties into uneven surfaces, 2) prevent excessive protrusion of the resin material from the periphery of the substrate during lamination, 3) reduce the curing temperature, 4) reduce the dielectric tangent of the cured product, 5) improve adhesion to metals, and 6) improve the bending stability of the cured product. Another object of the present invention is to provide a laminate film and a multilayer printed wiring board using the above resin material. [Means for solving the problem]

[0011] According to a broad aspect of the present invention, there is provided a resin material including a polyimide compound and at least one aliphatic skeleton-containing compound selected from the group consisting of a maleimide compound having an aliphatic skeleton and a benzoxazine compound having an aliphatic skeleton.

[0012] In a specific aspect of the present invention, in the aliphatic skeleton-containing compound, the aliphatic skeleton is bonded to a nitrogen atom forming a maleimide skeleton or a benzoxazine skeleton.

[0013] In a specific aspect of the present invention, the polyimide compound has a weight average molecular weight of 15,000 or more, and the aliphatic skeleton-containing compound has a weight average molecular weight of less than 15,000.

[0014] In a specific aspect of the resin material according to the present invention, the aliphatic skeleton-containing compound has a skeleton derived from a reaction product of a polyamine compound having an aliphatic skeleton and a carboxylic dianhydride.

[0015] In a specific aspect of the resin material according to the present invention, the aliphatic skeleton-containing compound has a skeleton derived from a reaction product of a diamine compound having an aliphatic skeleton and a carboxylic acid dianhydride.

[0016] In a specific aspect of the resin material according to the present invention, the diamine compound having an aliphatic skeleton is a diamine compound having a skeleton derived from dimer diamine.

[0017] In a specific aspect of the resin material according to the present invention, the resin material includes a thermosetting compound and an inorganic filler.

[0018] In a specific aspect of the resin material according to the present invention, the thermosetting compound is an epoxy compound.

[0019] In a specific aspect of the resin material according to the present invention, the content of the inorganic filler is 50% by weight or more in 100% by weight of the components excluding the solvent in the resin material.

[0020] In a specific aspect of the resin material according to the present invention, the content of the polyimide compound is 3% by weight or more and 80% by weight or less, based on 100% by weight of the total of the polyimide compound and the aliphatic skeleton-containing compound.

[0021] In a specific aspect of the resin material according to the present invention, the polyimide compound has a skeleton derived from dimer diamine.

[0022] In a specific aspect of the resin material according to the present invention, the total content of the polyimide compound and the aliphatic skeleton-containing compound is 10% by weight or more and 98% by weight or less, based on 100% by weight of organic components excluding the solvent in the resin material.

[0023] In a specific aspect of the resin material according to the present invention, the resin material includes a curing accelerator, and the curing accelerator includes at least one of a radical curing accelerator and an anionic curing accelerator.

[0024] In a specific aspect of the resin material according to the present invention, the curing accelerator includes a radical curing accelerator and dimethylaminopyridine, or includes a radical curing accelerator and an imidazole compound, or includes a radical curing accelerator and a phosphorus compound.

[0025] In a specific aspect of the resin material according to the present invention, the resin material includes a curing agent and a curing accelerator, and the curing accelerator includes an imidazole compound.

[0026] In a specific aspect of the resin material according to the present invention, the resin material is a resin film.

[0027] The resin material according to the present invention is suitably used for forming an insulating layer in a multilayer printed wiring board.

[0028] According to a broad aspect of the present invention, there is provided a laminate film comprising a substrate and a resin film laminated on a surface of the substrate, the resin film being made of the resin material described above.

[0029] According to a broad aspect of the present invention, there is provided a multilayer printed wiring board comprising a circuit board, a plurality of insulating layers disposed on a surface of the circuit board, and a metal layer disposed between the plurality of insulating layers, wherein at least one of the plurality of insulating layers is a cured product of the resin material described above. Effect of the Invention

[0030] The resin material according to the present invention contains a polyimide compound and at least one aliphatic skeleton-containing compound selected from a maleimide compound having an aliphatic skeleton and a benzoxazine compound having an aliphatic skeleton. The resin material according to the present invention has the above-mentioned configuration, and therefore can 1) improve embedding properties into uneven surfaces, 2) prevent excessive protrusion of the resin material from the periphery of the substrate during lamination, 3) keep the curing temperature low, 4) reduce the dielectric tangent of the cured product, 5) improve adhesion to metals, and 6) improve the bending stability of the cured product. The resin material according to the present invention can achieve all of the above effects 1)-6). [Brief description of the drawings]

[0031] [Figure 1] FIG. 1 is a cross-sectional view showing a schematic diagram of a multilayer printed wiring board using a resin material according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0032] The present invention will be described in detail below.

[0033] The resin material according to the present invention contains a polyimide compound and at least one aliphatic skeleton-containing compound selected from a maleimide compound having an aliphatic skeleton and a benzoxazine compound having an aliphatic skeleton.

[0034] The resin material according to the present invention has the above-mentioned configuration, and therefore 1) improves embedding ability into uneven surfaces, 2) prevents excessive protrusion of the resin material from the periphery of the substrate during lamination, 3) keeps the curing temperature low, 4) reduces the dielectric tangent of the cured product, 5) improves adhesion to metals, and 6) improves the bending stability of the cured product. The resin material according to the present invention can achieve all of the above effects 1)-6). The resin material according to the present invention can improve 5) adhesion to metals, for example, by increasing the peel strength between an insulating layer and a metal layer (copper layer).

[0035] In addition, since the resin material according to the present invention has the above-mentioned configuration, it is possible to improve the thermal dimensional stability.In addition, since the resin material according to the present invention has the above-mentioned configuration, it is possible to improve the handleability.

[0036] The resin material according to the present invention may be a resin composition or a resin film. The resin composition has fluidity. The resin composition may be in a paste form. The paste form includes a liquid form. Since the resin material according to the present invention is excellent in handleability, it is preferable that the resin material according to the present invention is a resin film. When the resin material according to the present invention is a resin composition, the handleability during application or film formation can be improved. When the resin material according to the present invention is a resin film, the handleability during lamination can be improved.

[0037] In particular, when both the polyimide compound and the aliphatic skeleton-containing compound have a structure represented by the following formula (X), the compatibility between the polyimide compound and the aliphatic skeleton-containing compound is improved, and the bending stability of the cured product can be further improved.

[0038] [ka]

[0039] In the above formula (X), R1 represents a tetravalent organic group.

[0040] The resin material according to the present invention is preferably a thermosetting material. When the resin material is a resin film, the resin film is preferably a thermosetting resin film.

[0041] In the present invention, the combination of a polyimide compound and a specific aliphatic skeleton-containing compound is an important and technically significant configuration. When a resin material contains a polyimide compound but does not contain a specific aliphatic skeleton-containing compound, it is difficult to effectively achieve all of the above-mentioned 1)-6) effects of the present invention. In particular, when a resin material contains a polyimide compound but does not contain a specific aliphatic skeleton-containing compound, it is difficult to improve embedding properties for uneven surfaces, lower the dielectric tangent, lower the curing temperature, and improve the bending stability of the cured product. In particular, when the maleimide compound is an N-phenylmaleimide compound (for example, a maleimide compound having a structure in which a plurality of maleimide skeletons and all nitrogen atoms are bonded to an aromatic ring), the N-phenylmaleimide compound has a high Tg, so it is difficult to lower the curing temperature and the dielectric tangent. On the other hand, when a resin material does not contain a polyimide compound but contains a specific aliphatic skeleton-containing compound, it is also difficult to effectively achieve all of the above-mentioned 1)-6) effects of the present invention. In particular, when the resin material does not contain a polyimide compound but contains a specific aliphatic skeleton-containing compound, the resin material may overflow from the periphery of the substrate during lamination, making it difficult to control the thickness of the insulating layer and contaminating the surrounding substrate. In addition, when the resin material is a resin film, the amount of flow during lamination may be large. As a result, the thickness of the insulating layer may become uneven.

[0042] Hereinafter, details of each component used in the resin material according to the present invention and applications of the resin material according to the present invention will be described.

[0043] [Polyimide compounds] The resin material according to the present invention includes a polyimide compound. The polyimide compound is a compound different from a maleimide compound. The polyimide compound may or may not have a maleimide skeleton at the end. The polyimide compound may have an acid anhydride structure or a citraconic imide structure at the end. As the polyimide compound, a conventionally known polyimide compound can be used. The polyimide compound may be used alone or in combination of two or more kinds.

[0044] The polyimide compound can be obtained by a method of reacting a tetracarboxylic dianhydride with an isocyanate ester compound, a method of reacting a tetracarboxylic dianhydride with a diamine compound, a method of reacting a tetracarboxylic dianhydride with a triamine compound, or the like.

[0045] Examples of the tetracarboxylic dianhydride include pyromellitic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-biphenylsulfone tetracarboxylic dianhydride, 1,4,5,8-naphthalene tetracarboxylic dianhydride, 2,3,6,7-naphthalene tetracarboxylic dianhydride, 3,3',4,4'-biphenyl ether tetracarboxylic dianhydride, 3,3',4,4'-dimethyldiphenylsilane tetracarboxylic dianhydride, 3,3',4,4'-tetraphenylsilane tetracarboxylic dianhydride, 1,2,3,4-furan tetracarboxylic dianhydride, 4,4'-bis(3,4-dicarboxyphenoxy)diphenylsulfonate, and 4,4'-bis(3,4-dicarboxyphenoxy)diphenylsulfonate. sulfide dianhydride, 4,4'-bis(3,4-dicarboxyphenoxy)diphenylsulfone dianhydride, 4,4'-bis(3,4-dicarboxyphenoxy)diphenylpropane dianhydride, 3,3',4,4'-perfluoroisopropylidenediphthalic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, bis(phthalic acid)phenylphosphine oxide dianhydride, p-phenylene-bis(triphenylphthalic acid) dianhydride, m-phenylene-bis(triphenylphthalic acid) dianhydride, bis(triphenylphthalic acid)-4,4'-diphenyl ether dianhydride, and bis(triphenylphthalic acid)-4,4'-diphenylmethane dianhydride.

[0046] Examples of the diamine compound include 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, bis(aminomethyl)norbornane, 3(4),8(9)-bis(aminomethyl)tricyclo[5.2.1.02,6]decane, 1,1-bis(4-aminophenyl)cyclohexane, 1,3-cyclohexanediamine, 1,4-cyclohexanediamine, 2,7-diaminofluorene, 4,4'-ethylenedianiline, isophoronediamine, 4,4'-methylenebis(cyclohexylamine), 4, Examples of the diaminophenylamine include 4'-methylenebis(2,6-diethylaniline), 4,4'-methylenebis(2-ethyl-6-methylaniline), 4,4'-methylenebis(2-methylcyclohexylamine), 1,4-diaminobutane, 1,10-diaminodecane, 1,12-diaminododecane, 1,7-diaminoheptane, 1,6-diaminohexane, 1,5-diaminopentane, 1,8-diaminooctane, 1,3-diaminopropane, 1,11-diaminoundecane, 2-methyl-1,5-diaminopentane, and dimer diamine.

[0047] An imide skeleton is formed by the reaction between the tetracarboxylic dianhydride and the diamine compound.

[0048] From the viewpoint of effectively exerting the above-mentioned effects 1)-6) of the present invention, the polyimide compound is preferably a polyimide compound having a skeleton derived from dimer diamine. The skeleton derived from dimer diamine is present as a partial skeleton in the polyimide compound.

[0049] The polyimide compound having a skeleton derived from dimer diamine is preferably obtained by reacting the tetracarboxylic dianhydride with the dimer diamine.

[0050] Examples of the dimer diamine include VERSAMINE 551 (trade name, manufactured by BASF Japan, 3,4-bis(1-aminoheptyl)-6-hexyl-5-(1-octenyl)cyclohexene), VERSAMINE 552 (trade name, manufactured by Cognics Japan, hydrogenated VERSAMINE 551), PRIAMINE 1075, and PRIAMINE 1074 (trade names, all manufactured by Croda Japan).

[0051] In the total of 100% by weight of the polyimide compound and the aliphatic skeleton-containing compound, the content of the polyimide compound is preferably 3% by weight or more, more preferably 5% by weight or more, even more preferably 10% by weight or more, preferably 80% by weight or less, more preferably 60% by weight or less, and even more preferably 50% by weight or less. When the content of the polyimide compound is above the lower limit and below the upper limit, the viscosity of the resin material does not become too high, and the handling property and embedding property into the uneven surface can be further improved. In addition, when the content of the polyimide compound is above the lower limit and below the upper limit, the flow amount during lamination can be suppressed from becoming too large.

[0052] The content of the polyimide compound in 100% by weight of the components in the resin material excluding the inorganic filler and the solvent is preferably 3% by weight or more, more preferably 5% by weight or more, and even more preferably 7% by weight or more. The content of the polyimide compound in 100% by weight of the components in the resin material excluding the inorganic filler and the solvent is preferably 40% by weight or less, more preferably 30% by weight or less, even more preferably 25% by weight or less, and particularly preferably 20% by weight or less. When the content of the polyimide compound is equal to or more than the lower limit, the dielectric tangent of the cured product can be lowered, the flow amount can be well controlled, and the adhesion between the insulating layer and the metal layer can be further improved. When the content of the polyimide compound is equal to or less than the upper limit, the embedding property for the uneven surface can be further improved. When the content of the polyimide compound is equal to or more than the lower limit and equal to or less than the upper limit, the handleability can be improved.

[0053] From the viewpoint of further improving embedding ability into uneven surfaces, the weight average molecular weight of the polyimide compound is preferably 15,000 or more, more preferably 20,000 or more, and preferably less than 50,000, more preferably less than 40,000.

[0054] The weight average molecular weight of the polyimide compound means a molecular weight that can be calculated from the structural formula when the polyimide compound is not a polymer and when the structural formula of the polyimide compound can be specified. When the polyimide compound is a polymer, the weight average molecular weight of the polyimide compound means a weight average molecular weight in terms of polystyrene measured by gel permeation chromatography (GPC).

[0055] When the polyimide compound has a maleimide skeleton at its terminal, the weight-weight molecular weight of the polyimide compound is preferably 15,000 or more, and more preferably 20,000 or more.

[0056] [Aliphatic skeleton-containing compounds] The resin material according to the present invention includes an aliphatic skeleton-containing compound. The aliphatic skeleton-containing compound is at least one of a maleimide compound having an aliphatic skeleton and a benzoxazine compound having an aliphatic skeleton. The resin material according to the present invention may include only a maleimide compound having an aliphatic skeleton, or only a benzoxazine compound having an aliphatic skeleton, as the aliphatic skeleton-containing compound, or may include both a maleimide compound having an aliphatic skeleton and a benzoxazine compound having an aliphatic skeleton.

[0057] <Maleimide compounds having an aliphatic skeleton> The resin material according to the present invention preferably contains a maleimide compound having an aliphatic skeleton (hereinafter, may be referred to as maleimide compound X) as an aliphatic skeleton-containing compound. The maleimide compound X is a compound different from a polyimide compound. The maleimide compound X has a maleimide group. The maleimide compound X has a maleimide group at a terminal. The maleimide compound X has an aliphatic skeleton. Therefore, the maleimide compound X has a maleimide group and an aliphatic skeleton. In the maleimide compound X, it is preferable that the aliphatic skeleton is bonded to a nitrogen atom forming the maleimide skeleton. The maleimide compound X may have an imide skeleton. As the maleimide compound X, a conventionally known maleimide compound can be used. The maleimide compound X includes a citraconic imide compound. The citraconic imide compound is a compound in which a methyl group is bonded to one of the carbon atoms constituting the double bond between carbon atoms in the maleimide group. The maleimide compound X may have a citraconic imide structure at a terminal. The maleimide compound X may be used alone or in combination of two or more kinds.

[0058] The maleimide compound X preferably has a skeleton derived from a reaction product of a polyamine compound having an aliphatic skeleton and a carboxylic dianhydride. The polyamine compound means a compound having two or more primary amino groups. The maleimide compound X may have a skeleton derived from a reaction product of a polyamine compound having an aliphatic skeleton and a carboxylic dianhydride, or may have a skeleton derived from a reaction product of a polyamine compound having an aliphatic skeleton, an amine compound different from the polyamine compound having an aliphatic skeleton, and a carboxylic dianhydride.

[0059] The maleimide compound X having a skeleton derived from a reaction product of a polyamine compound having an aliphatic skeleton and a carboxylic dianhydride can be obtained, for example, by reacting a polyamine compound having an aliphatic skeleton with a carboxylic dianhydride to obtain a reaction product having amino groups at both ends, and then reacting the reaction product with maleic anhydride.

[0060] Specifically, the maleimide compound X preferably has a skeleton derived from a reaction product of a diamine compound having an aliphatic skeleton or a triamine compound having an aliphatic skeleton and a carboxylic dianhydride. The maleimide compound X may have a skeleton derived from a reaction product of a diamine compound having an aliphatic skeleton and a carboxylic dianhydride. The maleimide compound X may have a skeleton derived from a reaction product of a diamine compound having an aliphatic skeleton, an amine compound (e.g., a diamine compound having an aromatic skeleton) different from the diamine compound having an aliphatic skeleton, and a carboxylic dianhydride. The maleimide compound X may have a skeleton derived from a reaction product of a triamine compound having an aliphatic skeleton and a carboxylic dianhydride, or may have a skeleton derived from a reaction product of a triamine compound having an aliphatic skeleton, an amine compound different from the triamine compound having an aliphatic skeleton, and a carboxylic dianhydride. In this case, it is preferable that one of a diamine compound having an aliphatic skeleton and a triamine compound having an aliphatic skeleton is used to obtain the reaction product. It is more preferable that both a diamine compound having an aliphatic skeleton and a triamine compound having an aliphatic skeleton are used to obtain the reaction product. In this case, the blending amount (wt %) of the triamine compound having an aliphatic skeleton is preferably 5% or less of the blending amount (wt %) of the diamine compound having an aliphatic skeleton.

[0061] The maleimide compound X having a skeleton derived from a reaction product of a diamine compound having an aliphatic skeleton and a carboxylic dianhydride can be obtained, for example, by reacting a diamine compound having an aliphatic skeleton with a carboxylic dianhydride to obtain a reaction product having amino groups at both ends, and then reacting the reaction product with maleic anhydride.

[0062] The maleimide compound X having a skeleton derived from a reaction product of a triamine compound having an aliphatic skeleton and a carboxylic dianhydride can be obtained, for example, by reacting a triamine compound having an aliphatic skeleton with a carboxylic dianhydride to obtain a reaction product having amino groups at both ends, and then reacting the reaction product with maleic anhydride.

[0063] When the maleimide compound X is a reaction product of a diamine compound and a carboxylic dianhydride, the maleimide compound X preferably satisfies the following (1) or (2), and more preferably satisfies (1) and (2): (1) It has a diamine skeleton at both ends; (2) In the amino group of the diamine compound that is not directly bonded to the carboxylic dianhydride, the skeleton having the amino group is a maleimide skeleton.

[0064] Examples of the diamine compound having an aliphatic skeleton include 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, bis(aminomethyl)norbornane, 3(4),8(9)-bis(aminomethyl)tricyclo[5.2.1.02,6]decane, 1,3-cyclohexanediamine, 1,4-cyclohexanediamine, isophoronediamine, 4,4'-methylenebis(cyclohexylamine), 4,4'-methylphenyl ... Examples of the diamine compounds include diamine compounds having a skeleton derived from ethylene bis(2-methylcyclohexylamine), 1,4-diaminobutane, 1,10-diaminodecane, 1,12-diaminododecane, 1,7-diaminoheptane, 1,6-diaminohexane, 1,5-diaminopentane, 1,8-diaminooctane, 1,3-diaminopropane, 1,11-diaminoundecane, 2-methyl-1,5-diaminopentane, and dimer diamine.

[0065] Examples of the diamine compound having an aromatic skeleton include 1,1-bis(4-aminophenyl)cyclohexane, 2,7-diaminofluorene, 4,4'-ethylenedianiline, 4,4'-methylenebis(2,6-diethylaniline), and 4,4'-methylenebis(2-ethyl-6-methylaniline).

[0066] Examples of the carboxylic acid dianhydride include pyromellitic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-biphenylsulfone tetracarboxylic dianhydride, 1,4,5,8-naphthalene tetracarboxylic dianhydride, 2,3,6,7-naphthalene tetracarboxylic dianhydride, 3,3',4,4'-biphenyl ether tetracarboxylic dianhydride, 3,3',4,4'-dimethyldiphenylsilane tetracarboxylic dianhydride, 3,3',4,4'-tetraphenylsilane tetracarboxylic dianhydride, 1,2,3,4-furan tetracarboxylic dianhydride, 4,4'-bis(3,4-dicarboxyphenoxy)diphenylsulfonate, and 4,4'-bis(3,4-dicarboxyphenoxy)diphenylsulfonate. dianhydride, 4,4'-bis(3,4-dicarboxyphenoxy)diphenylsulfone dianhydride, 4,4'-bis(3,4-dicarboxyphenoxy)diphenylpropane dianhydride, 3,3',4,4'-perfluoroisopropylidenediphthalic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, bis(phthalic acid)phenylphosphine oxide dianhydride, p-phenylene-bis(triphenylphthalic acid) dianhydride, m-phenylene-bis(triphenylphthalic acid) dianhydride, bis(triphenylphthalic acid)-4,4'-diphenyl ether dianhydride, and bis(triphenylphthalic acid)-4,4'-diphenylmethane dianhydride.

[0067] From the viewpoint of lowering the dielectric tangent, the diamine compound having an aliphatic skeleton is preferably a diamine compound having a skeleton derived from dimer diamine.

[0068] The diamine compound having a skeleton derived from the dimer diamine is preferably a reaction product of the dimer diamine and a tetracarboxylic dianhydride. When the diamine compound having a skeleton derived from the dimer diamine is a reaction product of the dimer diamine and a tetracarboxylic dianhydride, the reaction product (the diamine compound) may have a diamine skeleton other than the skeleton derived from the dimer diamine.

[0069] Examples of the dimer diamine include VERSAMINE 551 (trade name, manufactured by BASF Japan, 3,4-bis(1-aminoheptyl)-6-hexyl-5-(1-octenyl)cyclohexene), VERSAMINE 552 (trade name, manufactured by Cognics Japan, hydrogenated VERSAMINE 551), PRIAMINE 1075, and PRIAMINE 1074 (trade names, all manufactured by Croda Japan).

[0070] Examples of the tetracarboxylic dianhydride include pyromellitic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-biphenylsulfone tetracarboxylic dianhydride, 1,4,5,8-naphthalene tetracarboxylic dianhydride, 2,3,6,7-naphthalene tetracarboxylic dianhydride, 3,3',4,4'-biphenyl ether tetracarboxylic dianhydride, 3,3',4,4'-dimethyldiphenylsilane tetracarboxylic dianhydride, 3,3',4,4'-tetraphenylsilane tetracarboxylic dianhydride, 1,2,3,4-furan tetracarboxylic dianhydride, 4,4'-bis(3,4-dicarboxyphenoxy)diphenylsulfonate, and 4,4'-bis(3,4-dicarboxyphenoxy)diphenylsulfonate. sulfide dianhydride, 4,4'-bis(3,4-dicarboxyphenoxy)diphenylsulfone dianhydride, 4,4'-bis(3,4-dicarboxyphenoxy)diphenylpropane dianhydride, 3,3',4,4'-perfluoroisopropylidenediphthalic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, bis(phthalic acid)phenylphosphine oxide dianhydride, p-phenylene-bis(triphenylphthalic acid) dianhydride, m-phenylene-bis(triphenylphthalic acid) dianhydride, bis(triphenylphthalic acid)-4,4'-diphenyl ether dianhydride, and bis(triphenylphthalic acid)-4,4'-diphenylmethane dianhydride.

[0071] In order to more effectively exert the effects of the present invention in the above items 1)-6), the maleimide compound X is preferably an N-alkylbismaleimide compound having a skeleton derived from dimer diamine.

[0072] Commercially available N-alkylbismaleimide compounds having a skeleton derived from the above dimer diamine include "BMI-1500," "BMI-1700," and "BMI-3000" manufactured by Designer Molecules Inc.

[0073] The weight ratio of the content of the maleimide compound X to the total content of the thermosetting compound and component X is preferably 0.05 or more, more preferably 0.1 or more, and preferably 0.9 or less, more preferably 0.75 or less. When the weight ratio (the content of the maleimide compound X / the total content of the thermosetting compound and component X) is equal to or more than the lower limit and equal to or less than the upper limit, the dielectric tangent can be further reduced, and the adhesion between the insulating layer and the metal layer can be further improved.

[0074] The content of the maleimide compound X in 100% by weight of the components in the resin material excluding the inorganic filler and the solvent is preferably 3% by weight or more, more preferably 5% by weight or more, even more preferably 10% by weight or more, preferably 90% by weight or less, more preferably 80% by weight or less. When the content of the maleimide compound X is equal to or more than the lower limit, the dielectric tangent can be further lowered, and the adhesion between the insulating layer and the metal layer can be further improved. When the content of the maleimide compound X is equal to or less than the upper limit, the embeddability during lamination can be improved.

[0075] From the viewpoint of further enhancing the adhesion between the insulating layer and the metal layer, the weight average molecular weight of the maleimide compound X is preferably 500 or more, more preferably 1,000 or more, and preferably less than 15,000, more preferably less than 12,000, and even more preferably less than 10,000.

[0076] The weight average molecular weight of the maleimide compound X means a molecular weight that can be calculated from the structural formula when the maleimide compound X is not a polymer and when the structural formula of the maleimide compound X can be specified. When the maleimide compound X is a polymer, the weight average molecular weight of the maleimide compound X means a weight average molecular weight calculated in terms of polystyrene measured by gel permeation chromatography (GPC).

[0077] <Benzoxazine compounds having an aliphatic skeleton> The resin material according to the present invention preferably contains a benzoxazine compound having an aliphatic skeleton (hereinafter, may be referred to as benzoxazine compound X) as an aliphatic skeleton-containing compound. The benzoxazine compound X has a benzoxazine skeleton. Therefore, the benzoxazine compound X has a benzoxazine skeleton and an aliphatic skeleton. In the benzoxazine compound X, it is preferable that the aliphatic skeleton is bonded to a nitrogen atom forming the benzoxazine skeleton. The benzoxazine compound X may have an imide skeleton. As the benzoxazine compound X, a conventionally known benzoxazine compound can be used. The benzoxazine compound X may be used alone or in combination of two or more kinds.

[0078] The benzoxazine compound X includes an N-alkylbenzoxazine compound.

[0079] The benzoxazine compound X is preferably a compound in which the maleimide skeleton of the maleimide compound X described above is substituted with a benzoxazine skeleton.

[0080] The benzoxazine compound X can be obtained, for example, by reacting the above-mentioned tetracarboxylic dianhydride with the above-mentioned diamine compound to obtain a reaction product having amino groups at both ends, and then reacting the reaction product with phenol and paraformaldehyde. The N-alkylbenzoxazine compound having a skeleton derived from dimer diamine can be obtained, for example, by reacting tetracarboxylic dianhydride with dimer diamine to obtain a reaction product having a skeleton derived from dimer diamine at both ends, and then reacting the reaction product with phenol and paraformaldehyde.

[0081] The benzoxazine compound X preferably has an imide skeleton in the main chain, which can enhance compatibility with the polyimide compound, thereby further improving the bending stability of the cured product.

[0082] The benzoxazine compound X preferably has a skeleton derived from a reaction product of a polyamine compound having an aliphatic skeleton and a carboxylic dianhydride. The polyamine compound means a compound having two or more primary amino groups. The benzoxazine compound X may have a skeleton derived from a reaction product of a polyamine compound having an aliphatic skeleton and a carboxylic dianhydride, or may have a skeleton derived from a reaction product of a polyamine compound having an aliphatic skeleton, an amine compound different from the polyamine compound having an aliphatic skeleton, and a carboxylic dianhydride.

[0083] The benzoxazine compound X having a skeleton derived from a reaction product of a polyamine compound having an aliphatic skeleton and a carboxylic dianhydride can be obtained, for example, by reacting a polyamine compound having an aliphatic skeleton with a carboxylic dianhydride to obtain a reaction product having amino groups at both ends, and then reacting the reaction product with phenol and paraformaldehyde.

[0084] Specifically, the benzoxazine compound X preferably has a skeleton derived from a reaction product of a diamine compound having an aliphatic skeleton or a triamine compound having an aliphatic skeleton and a carboxylic dianhydride. The benzoxazine compound X may have a skeleton derived from a reaction product of a diamine compound having an aliphatic skeleton and a carboxylic dianhydride. The benzoxazine compound X may have a skeleton derived from a reaction product of a diamine compound having an aliphatic skeleton, an amine compound (e.g., a diamine compound having an aromatic skeleton) different from the diamine compound having an aliphatic skeleton, and a carboxylic dianhydride. The benzoxazine compound X may have a skeleton derived from a reaction product of a triamine compound having an aliphatic skeleton and a carboxylic dianhydride, or may have a skeleton derived from a reaction product of a triamine compound having an aliphatic skeleton, an amine compound different from the triamine compound having an aliphatic skeleton, and a carboxylic dianhydride. In this case, it is preferable that one of a diamine compound having an aliphatic skeleton and a triamine compound having an aliphatic skeleton is used to obtain the reaction product. It is more preferable that both a diamine compound having an aliphatic skeleton and a triamine compound having an aliphatic skeleton are used to obtain the reaction product. In this case, the blending amount (wt %) of the triamine compound having an aliphatic skeleton is preferably 5% or less of the blending amount (wt %) of the diamine compound having an aliphatic skeleton.

[0085] The benzoxazine compound X having a skeleton derived from a reaction product of a diamine compound having an aliphatic skeleton and a carboxylic dianhydride can be obtained, for example, by reacting a diamine compound having an aliphatic skeleton with a carboxylic dianhydride to obtain a reaction product having amino groups at both ends, and then reacting the reaction product with phenol and paraformaldehyde.

[0086] The benzoxazine compound X having a skeleton derived from a reaction product of a triamine compound having an aliphatic skeleton and a carboxylic dianhydride can be obtained, for example, by reacting a triamine compound having an aliphatic skeleton with a carboxylic dianhydride to obtain a reaction product having amino groups at both ends, and then reacting the reaction product with phenol and paraformaldehyde.

[0087] Examples of the diamine compound having an aliphatic skeleton include the diamine compounds described above.

[0088] Examples of the diamine compound having an aromatic skeleton include the diamine compounds described above.

[0089] Examples of the carboxylic acid dianhydride include the carboxylic acid dianhydrides described above.

[0090] From the viewpoint of lowering the dielectric tangent, the diamine compound having an aliphatic skeleton is preferably a diamine compound having a skeleton derived from dimer diamine.

[0091] The diamine compound having a skeleton derived from the dimer diamine is preferably a reaction product of the dimer diamine and a tetracarboxylic dianhydride. When the diamine compound having a skeleton derived from the dimer diamine is a reaction product of the dimer diamine and a tetracarboxylic dianhydride, the reaction product (the diamine compound) may have a diamine skeleton other than the skeleton derived from the dimer diamine.

[0092] The dimer diamine may be the dimer diamine described above.

[0093] Examples of the tetracarboxylic dianhydride include the tetracarboxylic dianhydrides described above.

[0094] In order to more effectively exert the effects of the present invention in the above items 1) to 6), the benzoxazine compound X is preferably an N-alkylbisbenzoxazine compound having a skeleton derived from dimer diamine.

[0095] The weight ratio of the content of the benzoxazine compound X to the total content of the thermosetting compound and component X is preferably 0.05 or more, more preferably 0.1 or more, and preferably 0.9 or less, more preferably 0.75 or less. When the weight ratio (the content of the benzoxazine compound X / the total content of the thermosetting compound and component X) is equal to or more than the lower limit and equal to or less than the upper limit, the dielectric tangent can be further reduced, and the adhesion between the insulating layer and the metal layer can be further improved.

[0096] The content of the benzoxazine compound X in 100% by weight of the components in the resin material excluding the inorganic filler and the solvent is preferably 3% by weight or more, more preferably 5% by weight or more, even more preferably 10% by weight or more, preferably 90% by weight or less, more preferably 80% by weight or less. When the content of the benzoxazine compound X is equal to or more than the lower limit, the dielectric tangent can be further lowered, and the adhesion between the insulating layer and the metal layer can be further improved. When the content of the benzoxazine compound X is equal to or less than the upper limit, the embeddability during lamination can be improved.

[0097] From the viewpoint of further enhancing the adhesion between the insulating layer and the metal layer, the weight average molecular weight of the benzoxazine compound X is preferably 500 or more, more preferably 1,000 or more, and preferably less than 15,000, more preferably less than 12,000, and even more preferably less than 10,000.

[0098] The weight average molecular weight of the benzoxazine compound X means a molecular weight that can be calculated from the structural formula when the benzoxazine compound X is not a polymer and when the structural formula of the benzoxazine compound X can be specified. When the benzoxazine compound X is a polymer, the weight average molecular weight of the benzoxazine compound X indicates a weight average molecular weight in terms of polystyrene measured by gel permeation chromatography (GPC).

[0099] The total content of the polyimide compound and the aliphatic skeleton-containing compound in 100% by weight of the organic components excluding the solvent in the resin material is preferably 10% by weight or more, more preferably 15% by weight or more, and even more preferably 20% by weight or more. The total content of the polyimide compound and the aliphatic skeleton-containing compound in 100% by weight of the organic components excluding the solvent in the resin material is preferably 98% by weight or less, more preferably 80% by weight or less. When the total content is equal to or more than the lower limit and equal to or less than the upper limit, the effects of the present invention 1)-6) described above can be more effectively exhibited.

[0100] [Thermosetting compound] The resin material preferably contains a thermosetting compound. The thermosetting compound is a thermosetting compound different from the polyimide compound, the maleimide compound X, and the benzoxazine compound X. Examples of the thermosetting compound include styrene compounds, vinyl compounds, phenoxy compounds, oxetane compounds, epoxy compounds, episulfide compounds, (meth)acrylic compounds, phenol compounds, amino compounds, unsaturated polyester compounds, polyurethane compounds, and silicone compounds. The thermosetting compounds may be used alone or in combination of two or more.

[0101] From the viewpoint of more effectively exerting the above-mentioned effects 1) to 6) of the present invention and from the viewpoint of improving thermal dimensional stability, the thermosetting compound is preferably an epoxy compound.

[0102] Examples of the epoxy compound include bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, bisphenol S type epoxy compounds, phenol novolac type epoxy compounds, biphenyl type epoxy compounds, biphenyl novolac type epoxy compounds, biphenol type epoxy compounds, naphthalene type epoxy compounds, fluorene type epoxy compounds, phenol aralkyl type epoxy compounds, naphthol aralkyl type epoxy compounds, dicyclopentadiene type epoxy compounds, anthracene type epoxy compounds, epoxy compounds having an adamantane skeleton, epoxy compounds having a tricyclodecane skeleton, naphthylene ether type epoxy compounds, and epoxy compounds having a triazine nucleus in the skeleton.

[0103] The epoxy compound preferably contains an epoxy compound having an aromatic skeleton, more preferably contains an epoxy compound having a naphthalene skeleton or a phenyl skeleton, more preferably is an epoxy compound having an aromatic skeleton, and even more preferably is an epoxy compound having a naphthalene skeleton. In this case, the dielectric tangent can be further lowered, and the heat resistance, flame retardancy, and thermal dimensional stability can be improved.

[0104] From the viewpoint of further lowering the dielectric tangent and improving the coefficient of linear thermal expansion (CTE) of the cured product, it is preferable that the epoxy compound contains an epoxy compound that is liquid at 25°C and an epoxy compound that is solid at 25°C.

[0105] The viscosity at 25°C of the epoxy compound that is liquid at 25°C is preferably 1000 mPa·s or less, and more preferably 500 mPa·s or less.

[0106] When measuring the viscosity of the epoxy compound, for example, a dynamic viscoelasticity measuring device ("VAR-100" manufactured by Rheologica Instruments) is used.

[0107] It is more preferable that the molecular weight of the epoxy compound is 1000 or less. In this case, even if the resin material contains 100% by weight of components other than the solvent and contains 50% by weight or more of inorganic filler, a resin material with high fluidity can be obtained when forming an insulating layer. Therefore, when an uncured or B-staged resin material is laminated on a circuit board, the inorganic filler can be uniformly present.

[0108] The molecular weight of the epoxy compound means a molecular weight that can be calculated from the structural formula when the epoxy compound is not a polymer and when the structural formula of the epoxy compound can be specified, and means a weight average molecular weight when the epoxy compound is a polymer.

[0109] From the viewpoint of further increasing the adhesive strength between the cured product and the metal layer, the content of the above-mentioned epoxy compound in 100% by weight of the organic components excluding the solvent in the resin material is preferably 5% by weight or more, more preferably 25% by weight or more, preferably 50% by weight or less, more preferably 40% by weight or less.

[0110] The weight ratio of the content of the epoxy compound to the total content of the aliphatic skeleton-containing compound and the component X described later (the content of the epoxy compound / the total content of the aliphatic skeleton-containing compound and the component X described later) is preferably 0.1 or more, more preferably 0.2 or more. The weight ratio of the content of the epoxy compound to the total content of the aliphatic skeleton-containing compound and the component X described later (the content of the epoxy compound / the total content of the aliphatic skeleton-containing compound and the component X) is preferably 0.9 or less, more preferably 0.8 or less. When the weight ratio (the content of the epoxy compound / the total content of the aliphatic skeleton-containing compound and the component X) is equal to or more than the lower limit and equal to or less than the upper limit, the dielectric tangent can be lowered, the linear expansion coefficient can be reduced, the adhesion between the insulating layer and the metal layer can be further improved, and the handleability can be improved.

[0111] [Inorganic filler] The resin material preferably contains an inorganic filler. By using the inorganic filler, the dielectric tangent of the cured product can be further reduced. In addition, by using the inorganic filler, the dimensional change of the cured product due to heat can be further reduced. The inorganic filler may be used alone or in combination of two or more kinds.

[0112] Examples of the inorganic filler include silica, talc, clay, mica, hydrotalcite, alumina, magnesium oxide, aluminum hydroxide, aluminum nitride, and boron nitride.

[0113] From the viewpoint of reducing the surface roughness of the cured product, further increasing the adhesive strength between the cured product and the metal layer, forming finer wiring on the cured product surface, and imparting better insulation reliability to the cured product, the inorganic filler is preferably silica or alumina, more preferably silica, and even more preferably fused silica. By using silica, the thermal expansion coefficient of the cured product is further reduced, and the dielectric tangent of the cured product is further reduced. In addition, by using silica, the surface roughness of the cured product surface is effectively reduced, and the adhesive strength between the cured product and the metal layer is effectively increased. The shape of the silica is preferably spherical.

[0114] From the viewpoints of promoting resin curing regardless of the curing environment, effectively increasing the glass transition temperature of the cured product, and effectively reducing the coefficient of linear thermal expansion of the cured product, it is preferable that the inorganic filler be spherical silica.

[0115] The inorganic filler has an average particle size of preferably 50 nm or more, more preferably 100 nm or more, even more preferably 500 nm or more, and preferably 5 μm or less, more preferably 3 μm or less, and even more preferably 1 μm or less. When the inorganic filler has an average particle size of not less than the lower limit and not more than the upper limit, the fillability into uneven surfaces can be further improved, and the adhesion between the insulating layer and the metal layer can be further improved.

[0116] The median diameter (d50) at 50% is used as the average particle diameter of the inorganic filler. The average particle diameter can be measured using a particle size distribution measuring device using a laser diffraction scattering method.

[0117] The inorganic filler is preferably spherical, more preferably spherical silica. In this case, the surface roughness of the cured product is effectively reduced, and the adhesive strength between the cured product and the metal layer is effectively increased. When the inorganic filler is spherical, the aspect ratio of the inorganic filler is preferably 2 or less, more preferably 1.5 or less.

[0118] The inorganic filler is preferably surface-treated, more preferably surface-treated with a coupling agent, and even more preferably surface-treated with a silane coupling agent.By surface-treating the inorganic filler, the surface roughness of the roughened cured product is further reduced, and the adhesive strength between the cured product and the metal layer is further increased.In addition, by surface-treating the inorganic filler, finer wiring can be formed on the surface of the cured product, and better inter-wiring insulation reliability and inter-layer insulation reliability can be imparted to the cured product.

[0119] The coupling agent includes a silane coupling agent, a titanium coupling agent, an aluminum coupling agent, etc. The silane coupling agent includes a methacrylsilane, an acrylsilane, an aminosilane, an imidazole silane, a vinylsilane, an epoxysilane, etc.

[0120] The content of the inorganic filler in 100% by weight of the resin material excluding the solvent is preferably 50% by weight or more, more preferably 60% by weight or more, even more preferably 65% ​​by weight or more, and particularly preferably 68% by weight or more. The content of the inorganic filler in 100% by weight of the resin material excluding the solvent is preferably 90% by weight or less, more preferably 85% by weight or less, even more preferably 80% by weight or less, and particularly preferably 75% by weight or less. When the content of the inorganic filler is equal to or more than the lower limit, the dielectric tangent is effectively lowered and the linear expansion coefficient can be reduced. When the content of the inorganic filler is equal to or less than the upper limit, the adhesiveness, the embedding ability for uneven surfaces, and the etching performance can be improved. When the content of the inorganic filler is equal to or more than the lower limit and equal to or less than the upper limit, the surface roughness of the cured product can be further reduced, and finer wiring can be formed on the surface of the cured product. Furthermore, with this amount of inorganic filler, it is possible to lower the thermal expansion coefficient of the cured product and at the same time improve the smear removability.

[0121] [Hardening agent] The resin material preferably contains a curing agent. The curing agent is not particularly limited. As the curing agent, a conventionally known curing agent can be used. The curing agent may be used alone or in combination of two or more kinds.

[0122] Examples of the curing agent include cyanate ester compounds (cyanate ester curing agents), amine compounds (amine curing agents), thiol compounds (thiol curing agents), imidazole compounds, phosphine compounds, dicyandiamide, phenol compounds (phenol curing agents), acid anhydrides, active ester compounds, carbodiimide compounds (carbodiimide curing agents), benzoxazine compounds without an aliphatic skeleton (benzoxazine curing agents), and maleimide compounds without an aliphatic skeleton. The curing agent preferably has a functional group capable of reacting with the epoxy group of the epoxy compound.

[0123] From the viewpoint of lowering the dielectric tangent and increasing the thermal dimensional stability, the curing agent preferably contains at least one component selected from the group consisting of a phenolic compound, a cyanate ester compound, an acid anhydride, an active ester compound, a carbodiimide compound, and a benzoxazine compound having no aliphatic skeleton. That is, the resin material preferably contains a curing agent containing at least one component selected from the group consisting of a phenolic compound, a cyanate ester compound, an acid anhydride, an active ester compound, a carbodiimide compound, and a benzoxazine compound having no aliphatic skeleton. The benzoxazine compound having no aliphatic skeleton is preferably an N-phenylbenzoxazine compound in which an aromatic skeleton is bonded to a nitrogen atom forming a benzoxazine skeleton.

[0124] In this specification, "at least one component selected from a phenol compound, a cyanate ester compound, an acid anhydride, an active ester compound, a carbodiimide compound, and an N-phenylbenzoxazine compound in which an aromatic skeleton is bonded to a nitrogen atom forming a benzoxazine skeleton" may be referred to as "component X."

[0125] The resin material preferably contains a curing agent containing a component X. The component X may be used alone or in combination of two or more kinds.

[0126] Examples of the phenol compound include novolak type phenols, biphenol type phenols, naphthalene type phenols, dicyclopentadiene type phenols, aralkyl type phenols, and dicyclopentadiene type phenols.

[0127] Commercially available phenol compounds include novolac phenols ("TD-2091" manufactured by DIC Corporation), biphenyl novolac phenols ("MEH-7851" manufactured by Meiwa Kasei Co., Ltd.), aralkyl phenol compounds ("MEH-7800" manufactured by Meiwa Kasei Co., Ltd.), and phenols having an aminotriazine skeleton ("LA1356" and "LA3018-50P" manufactured by DIC Corporation).

[0128] Examples of the cyanate ester compound include novolac-type cyanate ester resins, bisphenol-type cyanate ester resins, and prepolymers obtained by partially trimerizing these. Examples of the novolac-type cyanate ester resins include phenol novolac-type cyanate ester resins and alkylphenol-type cyanate ester resins. Examples of the bisphenol-type cyanate ester resins include bisphenol A-type cyanate ester resins, bisphenol E-type cyanate ester resins, and tetramethylbisphenol F-type cyanate ester resins.

[0129] Commercially available products of the cyanate ester compound include phenol novolac type cyanate ester resins ("PT-30" and "PT-60" manufactured by Lonza Japan) and prepolymers in which bisphenol type cyanate ester resins are trimerized ("BA-230S", "BA-3000S", "BTP-1000S" and "BTP-6020S" manufactured by Lonza Japan).

[0130] Examples of the acid anhydride include tetrahydrophthalic anhydride and alkylstyrene-maleic anhydride copolymer.

[0131] Commercially available products of the above acid anhydrides include "Rikacid TDA-100" manufactured by New Japan Chemical Co., Ltd.

[0132] The above-mentioned active ester compound refers to a compound that contains at least one ester bond in the structure and has aromatic rings bonded to both sides of the ester bond. The active ester compound is obtained, for example, by a condensation reaction between a carboxylic acid compound or a thiocarboxylic acid compound and a hydroxy compound or a thiol compound. An example of the active ester compound is a compound represented by the following formula (1).

[0133] [ka]

[0134] In the above formula (1), X1 represents a group containing an aliphatic chain, a group containing an aliphatic ring, or a group containing an aromatic ring, and X2 represents a group containing an aromatic ring. Preferred examples of the group containing an aromatic ring include a benzene ring which may have a substituent, and a naphthalene ring which may have a substituent. Examples of the substituent include a hydrocarbon group. The number of carbon atoms in the hydrocarbon group is preferably 12 or less, more preferably 6 or less, and even more preferably 4 or less.

[0135] Examples of the combination of X1 and X2 include a combination of an optionally substituted benzene ring and an optionally substituted benzene ring, and a combination of an optionally substituted benzene ring and an optionally substituted naphthalene ring.Furthermore, examples of the combination of X1 and X2 include a combination of an optionally substituted naphthalene ring and an optionally substituted naphthalene ring.

[0136] The active ester compound is not particularly limited. From the viewpoint of further increasing the thermal dimensional stability, the active ester compound is preferably an active ester compound having two or more aromatic skeletons. From the viewpoint of decreasing the dielectric tangent of the cured product and increasing the thermal dimensional stability of the cured product, it is more preferable that the active ester has a naphthalene ring in the main chain skeleton.

[0137] Commercially available products of the above active ester compound include "HPC-8000-65T", "EXB9416-70BK", "EXB8100-65T", and "HPC-8150-60T" manufactured by DIC Corporation.

[0138] The carbodiimide compound has a structural unit represented by the following formula (2). In the following formula (2), the right end and the left end are bonding sites with other groups. The carbodiimide compound may be used alone or in combination of two or more kinds.

[0139] [ka]

[0140] In the above formula (2), X represents an alkylene group, a group in which a substituent is bonded to an alkylene group, a cycloalkylene group, a group in which a substituent is bonded to a cycloalkylene group, an arylene group, or a group in which a substituent is bonded to an arylene group, and p represents an integer of 1 to 5. When a plurality of Xs are present, the plurality of Xs may be the same or different.

[0141] In one preferred embodiment, at least one X is an alkylene group, a group in which a substituent is bonded to an alkylene group, a cycloalkylene group, or a group in which a substituent is bonded to a cycloalkylene group.

[0142] Commercially available examples of the carbodiimide compound include "Carbodilite V-02B", "Carbodilite V-03", "Carbodilite V-04K", "Carbodilite V-07", "Carbodilite V-09", "Carbodilite 10M-SP", and "Carbodilite 10M-SP (modified)" manufactured by Nisshinbo Chemical Inc., as well as "Stavaxol P", "Stavaxol P400", and "Hi-Kasil 510" manufactured by Rhein Chemie.

[0143] Examples of the benzoxazine compound not having an aliphatic skeleton include Pd-type benzoxazine and Fa-type benzoxazine.

[0144] Commercially available benzoxazine compounds not having an aliphatic skeleton include "Pd type" manufactured by Shikoku Chemical Industry Co., Ltd.

[0145] The content of the component X relative to 100 parts by weight of the total of the polyimide compound, the aliphatic skeleton-containing compound, and the thermosetting compound is preferably 70 parts by weight or more, more preferably 85 parts by weight or more, and preferably 150 parts by weight or less, and more preferably 120 parts by weight or less. When the content of the component X is equal to or more than the lower limit and equal to or less than the upper limit, the curability is more excellent, the thermal dimensional stability is further improved, and the volatilization of the remaining unreacted components can be further suppressed.

[0146] The content of the component X relative to 100 parts by weight of the thermosetting compound is preferably 70 parts by weight or more, more preferably 85 parts by weight or more, and preferably 150 parts by weight or less, and more preferably 120 parts by weight or less. When the content of the component X is equal to or more than the lower limit and equal to or less than the upper limit, the curability is more excellent, the thermal dimensional stability is further improved, and the volatilization of the remaining unreacted components can be further suppressed.

[0147] In 100% by weight of the components in the resin material excluding the inorganic filler and the solvent, the total content of the polyimide compound, the aliphatic skeleton-containing compound, the thermosetting compound, and the component X is preferably 50% by weight or more, more preferably 60% by weight or more, and preferably 90% by weight or less, and more preferably 85% by weight or less. When the total content of the thermosetting compound and the component X is equal to or more than the lower limit and equal to or less than the upper limit, the curability is more excellent and the thermal dimensional stability can be further improved.

[0148] In 100% by weight of the components in the resin material excluding the inorganic filler and the solvent, the total content of the thermosetting compound and the component X is preferably 50% by weight or more, more preferably 60% by weight or more, preferably 90% by weight or less, and more preferably 85% by weight or less. When the total content of the thermosetting compound and the component X is equal to or more than the lower limit and equal to or less than the upper limit, the curability is more excellent and the thermal dimensional stability can be further improved.

[0149] [Cure accelerator] The resin material preferably contains a curing accelerator. The use of the curing accelerator further increases the curing speed. By quickly curing the resin material, the crosslinked structure in the cured product becomes uniform, and the number of unreacted functional groups decreases, resulting in a high crosslink density. The curing accelerator is not particularly limited, and conventionally known curing accelerators can be used. The curing accelerator may be used alone or in combination of two or more.

[0150] Examples of the curing accelerator include anionic curing accelerators such as imidazole compounds, cationic curing accelerators such as amine compounds, curing accelerators other than anionic and cationic curing accelerators such as phosphorus compounds and organometallic compounds, and radical curing accelerators such as peroxides.

[0151] Examples of the imidazole compound include 2-undecylimidazole, 2-heptadecylimidazole, 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1,2-dimethylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, and 1-cyanoethyl-2-phenylimidazolium trimethylolate. remellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-methylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, and 2-phenyl-4-methyl-5-dihydroxymethylimidazole.

[0152] Examples of the amine compound include diethylamine, triethylamine, diethylenetetramine, triethylenetetramine, and 4,4-dimethylaminopyridine.

[0153] The phosphorus compound includes a triphenylphosphine compound.

[0154] Examples of the organometallic compound include zinc naphthenate, cobalt naphthenate, tin octoate, cobalt octoate, cobalt bisacetylacetonate (II), and cobalt trisacetylacetonate (III).

[0155] The peroxides include dicumyl peroxide and Perhexyl 25B.

[0156] From the viewpoint of further reducing the curing temperature, the curing accelerator preferably contains the anionic curing accelerator, and more preferably contains the imidazole compound.

[0157] From the viewpoint of further reducing the curing temperature, the content of the anionic curing accelerator in 100% by weight of the curing accelerator is preferably 50% by weight or more, more preferably 70% by weight or more, even more preferably 80% by weight or more, and most preferably 100% by weight (total amount).

[0158] The curing accelerator preferably contains at least one of a radical curing accelerator and an anionic curing accelerator. The anionic curing accelerator is preferably an imidazole compound. The curing accelerator preferably contains a radical curing accelerator and dimethylaminopyridine, or a radical curing accelerator and an imidazole compound, or a radical curing accelerator and a phosphorus compound. When the curing of the resin material does not proceed sufficiently, the dielectric loss tangent may become high and the linear expansion coefficient may become large. The curing accelerator may contain the radical curing accelerator and the imidazole compound. As the radical curing accelerator, it is preferable that the reaction temperature in the presence of the radical curing accelerator is higher than the provisional curing temperature before etching and lower than the main curing temperature after etching. When Perhexyl 25B is used as the radical curing accelerator, the above effect is more effectively exerted.

[0159] When the curing accelerator contains a radical curing accelerator and an imidazole compound, or contains a radical curing accelerator and a phosphorus compound, the curing of the resin material can be smoothly progressed, and a better cured product can be obtained.

[0160] The curing accelerator may include a radical curing accelerator and at least one curing accelerator selected from the group consisting of dimethylaminopyridine, an imidazole compound, and a phosphorus compound.

[0161] The content of the curing accelerator is not particularly limited. In 100% by weight of the components in the resin material excluding the inorganic filler and the solvent, the content of the curing accelerator is preferably 0.01% by weight or more, more preferably 0.05% by weight or more, preferably 5% by weight or less, more preferably 3% by weight or less. When the content of the curing accelerator is equal to or more than the lower limit and equal to or less than the upper limit, the resin material is cured efficiently. When the content of the curing accelerator is within a more preferred range, the storage stability of the resin material is further increased, and a better cured product is obtained.

[0162] [Thermoplastic resin] The resin material preferably contains a thermoplastic resin. Examples of the thermoplastic resin include polyvinyl acetal resin and phenoxy resin. The thermoplastic resin may be used alone or in combination of two or more kinds.

[0163] From the viewpoint of effectively lowering the dielectric tangent and effectively increasing the adhesion of the metal wiring regardless of the curing environment, the thermoplastic resin is preferably a phenoxy resin. By using the phenoxy resin, the deterioration of the embedding ability of the resin film in the holes or irregularities of the circuit board and the non-uniformity of the inorganic filler are suppressed. In addition, by using the phenoxy resin, the melt viscosity can be adjusted, so that the dispersibility of the inorganic filler is improved, and the resin composition or the B-stage product is less likely to wet and spread to unintended areas during the curing process.

[0164] The phenoxy resin contained in the resin material is not particularly limited. As the phenoxy resin, a conventionally known phenoxy resin can be used. The phenoxy resin may be used alone or in combination of two or more kinds.

[0165] Examples of the phenoxy resin include phenoxy resins having a skeleton such as a bisphenol A skeleton, a bisphenol F skeleton, a bisphenol S skeleton, a biphenyl skeleton, a novolac skeleton, a naphthalene skeleton, and an imide skeleton.

[0166] Commercially available examples of the phenoxy resin include "YP50", "YP55" and "YP70" manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd., and "1256B40", "4250", "4256H40", "4275", "YX6954BH30" and "YX8100BH30" manufactured by Mitsubishi Chemical Corporation.

[0167] From the viewpoint of obtaining a resin material having even better storage stability, the weight average molecular weight of the thermoplastic resin and the phenoxy resin is preferably 5,000 or more, more preferably 10,000 or more, and preferably 100,000 or less, more preferably 50,000 or less.

[0168] The weight average molecular weights of the thermoplastic resin and the phenoxy resin are weight average molecular weights measured by gel permeation chromatography (GPC) and calculated as polystyrene.

[0169] The contents of the thermoplastic resin and the phenoxy resin are not particularly limited. In 100% by weight of the components in the resin material excluding the inorganic filler and the solvent, the content of the thermoplastic resin (the content of the phenoxy resin when the thermoplastic resin is a phenoxy resin) is preferably 1% by weight or more, more preferably 2% by weight or more, preferably 30% by weight or less, more preferably 20% by weight or less. When the content of the thermoplastic resin is equal to or more than the lower limit and equal to or less than the upper limit, the resin material has good embedding properties in holes or irregularities in a circuit board. When the content of the thermoplastic resin is equal to or more than the lower limit, the formation of a resin film becomes easier, and a better insulating layer is obtained. When the content of the thermoplastic resin is equal to or less than the upper limit, the thermal expansion coefficient of the cured product becomes even lower. When the content of the thermoplastic resin is equal to or less than the upper limit, the surface roughness of the surface of the cured product becomes even smaller, and the adhesive strength between the cured product and the metal layer becomes even higher.

[0170] [solvent] The resin material does not contain or contains a solvent. By using the solvent, the viscosity of the resin material can be controlled within a suitable range, and the coatability of the resin material can be improved. The solvent may be used to obtain a slurry containing the inorganic filler. The solvent may be used alone or in combination of two or more.

[0171] Examples of the solvent include acetone, methanol, ethanol, butanol, 2-propanol, 2-methoxyethanol, 2-ethoxyethanol, 1-methoxy-2-propanol, 2-acetoxy-1-methoxypropane, toluene, xylene, methyl ethyl ketone, N,N-dimethylformamide, methyl isobutyl ketone, N-methyl-pyrrolidone, n-hexane, cyclohexane, cyclohexanone, and naphtha, which is a mixture.

[0172] Most of the solvent is preferably removed when the resin composition is molded into a film. Therefore, the boiling point of the solvent is preferably 200°C or less, more preferably 180°C or less. The content of the solvent in the resin composition is not particularly limited. The content of the solvent can be appropriately changed in consideration of the coatability of the resin composition.

[0173] [Other ingredients] For the purpose of improving impact resistance, heat resistance, resin compatibility, workability, and the like, the above-mentioned resin material may contain a leveling agent, a flame retardant, a coupling agent, a colorant, an antioxidant, an ultraviolet degradation inhibitor, a defoaming agent, a thickener, a thixotropy imparting agent, and a thermosetting resin other than the epoxy compound.

[0174] The coupling agent includes a silane coupling agent, a titanium coupling agent, an aluminum coupling agent, etc. The silane coupling agent includes a vinyl silane, an amino silane, an imidazole silane, an epoxy silane, etc.

[0175] Examples of the other thermosetting resins include polyphenylene ether resins, divinylbenzyl ether resins, polyarylate resins, diallyl phthalate resins, polyimide resins, benzoxazine resins, benzoxazole resins, bismaleimide resins, and acrylate resins.

[0176] (Resin film and laminated film) The above-mentioned resin composition is molded into a film to obtain a resin film (B-stage product / B-stage film). The above-mentioned resin material is preferably a resin film. The resin film is preferably a B-stage film.

[0177] The resin material is preferably a thermosetting material.

[0178] Examples of methods for forming a resin composition into a film to obtain a resin film include the following: an extrusion molding method in which a resin composition is melt-kneaded and extruded using an extruder, and then molded into a film using a T-die or a circular die; a casting molding method in which a resin composition containing a solvent is cast into a film; and other conventionally known film molding methods. The extrusion molding method and the casting molding method are preferred because they can be made thinner. Films include sheets.

[0179] The resin composition is molded into a film and dried by heating at, for example, 50 to 150° C. for 1 to 10 minutes to such an extent that curing by heat does not proceed too much, thereby obtaining a resin film that is a B-stage film.

[0180] The film-like resin composition obtained by the drying process as described above is called a B-stage film. The B-stage film is in a semi-cured state. The semi-cured product is not completely cured and can be further cured.

[0181] The resin film does not have to be a prepreg. When the resin film is not a prepreg, migration does not occur along the glass cloth, etc. In addition, when the resin film is laminated or precured, unevenness due to the glass cloth does not occur on the surface.

[0182] The above resin film can be suitably used in the form of a laminated film.

[0183] The laminated film includes a substrate and a resin film laminated on a surface of the substrate. The resin film is made of the resin material described above. The laminated film may include a protective film laminated on a surface of the resin film opposite to the substrate.

[0184] Examples of the substrate include polyester resin films such as polyethylene terephthalate film and polybutylene terephthalate film, olefin resin films such as polyethylene film and polypropylene film, polyimide resin films, and metal foils such as copper foil, etc. The surface of the substrate may be subjected to a release treatment as necessary.

[0185] From the viewpoint of controlling the degree of cure of the resin film more uniformly, the thickness of the resin film is preferably 5 μm or more and preferably 200 μm or less. When the resin film is used as an insulating layer of a circuit, the thickness of the insulating layer formed by the resin film is preferably equal to or more than the thickness of the conductor layer (metal layer) forming the circuit. The thickness of the insulating layer is preferably 5 μm or more and preferably 200 μm or less.

[0186] (Semiconductor devices, printed wiring boards, copper-clad laminates and multi-layer printed wiring boards) The above-mentioned resin material is suitably used for forming a molding resin in which a semiconductor chip is embedded in a semiconductor device.

[0187] The above-mentioned resin material is suitably used for forming an insulating layer in a printed wiring board.

[0188] The printed wiring board is obtained, for example, by hot-pressing and molding the resin material.

[0189] Metal foil can be laminated on one or both sides of the resin film. The method for laminating the resin film and the metal foil is not particularly limited, and a known method can be used. For example, the resin film can be laminated on the metal foil while applying pressure with or without heating using a device such as a parallel plate press or a roll laminator.

[0190] The resin material is preferably used to obtain a copper-clad laminate. An example of the copper-clad laminate is a copper-clad laminate including a copper foil and a resin film laminated on one surface of the copper foil.

[0191] The thickness of the copper foil of the copper-clad laminate is not particularly limited. The thickness of the copper foil is preferably within the range of 1 to 50 μm. In addition, in order to increase the adhesive strength between the cured product of the resin material and the copper foil, the copper foil preferably has fine irregularities on its surface. The method of forming the irregularities is not particularly limited. Examples of the method of forming the irregularities include a forming method by treatment using a known chemical solution.

[0192] The above resin materials are suitably used to obtain multi-layer substrates.

[0193] An example of the multilayer board is a multilayer board including a circuit board and an insulating layer laminated on the circuit board. The insulating layer of the multilayer board is formed of the resin material. The insulating layer of the multilayer board may be formed of the resin film of the laminate film by using a laminate film. The insulating layer is preferably laminated on the surface of the circuit board on which the circuit is provided. A part of the insulating layer is preferably embedded between the circuits.

[0194] In the multilayer board, the surface of the insulating layer opposite to the surface on which the circuit board is laminated is preferably roughened.

[0195] The roughening treatment method is not particularly limited and may be any conventionally known roughening treatment method. The surface of the insulating layer may be subjected to a swelling treatment before the roughening treatment.

[0196] Preferably, the multilayer substrate further comprises a copper plating layer laminated on the roughened surface of the insulating layer.

[0197] Another example of the multilayer board is a multilayer board comprising a circuit board, an insulating layer laminated on the surface of the circuit board, and a copper foil laminated on the surface of the insulating layer opposite to the surface on which the circuit board is laminated. The insulating layer is preferably formed by using a copper-clad laminate comprising copper foil and a resin film laminated on one surface of the copper foil, and curing the resin film. Furthermore, the copper foil is preferably etched to form a copper circuit.

[0198] Another example of the multilayer board is a multilayer board including a circuit board and a plurality of insulating layers laminated on a surface of the circuit board. At least one of the insulating layers arranged on the circuit board is formed using the resin material. The multilayer board preferably further includes a circuit laminated on at least one surface of the insulating layer formed using the resin film.

[0199] Among multilayer substrates, multilayer printed wiring boards are required to have a low dielectric tangent and high insulation reliability due to the insulating layer. The resin material according to the present invention can effectively improve insulation reliability by lowering the dielectric tangent and improving adhesion between the insulating layer and the metal layer and etching performance. Therefore, the resin material according to the present invention is suitably used for forming an insulating layer in a multilayer printed wiring board.

[0200] The multilayer printed wiring board includes, for example, a circuit board, a plurality of insulating layers disposed on a surface of the circuit board, and a metal layer disposed between the plurality of insulating layers, at least one of which is a cured product of the resin material.

[0201] FIG. 1 is a cross-sectional view showing a schematic diagram of a multilayer printed wiring board using a resin material according to one embodiment of the present invention.

[0202] In the multilayer printed wiring board 11 shown in FIG. 1, a plurality of insulating layers 13-16 are laminated on the upper surface 12a of the circuit board 12. The insulating layers 13-16 are cured layers. A metal layer 17 is formed on a partial region of the upper surface 12a of the circuit board 12. Of the plurality of insulating layers 13-16, the insulating layers 13-15 other than the insulating layer 16 located on the outer surface opposite to the circuit board 12 side have the metal layer 17 formed on a partial region of the upper surface. The metal layer 17 is a circuit. The metal layer 17 is disposed between the circuit board 12 and the insulating layer 13, and between each of the laminated insulating layers 13-16. The lower metal layer 17 and the upper metal layer 17 are connected to each other by at least one of a via hole connection and a through hole connection not shown.

[0203] In the multilayer printed wiring board 11, the insulating layers 13-16 are formed of a cured product of the above-mentioned resin material. In this embodiment, the surfaces of the insulating layers 13-16 are roughened, so that fine holes (not shown) are formed on the surfaces of the insulating layers 13-16. The metal layer 17 reaches the inside of the fine holes. In the multilayer printed wiring board 11, the width dimension (L) of the metal layer 17 and the width dimension (S) of the portion where the metal layer 17 is not formed can be reduced. In the multilayer printed wiring board 11, good insulation reliability is provided between the upper metal layer and the lower metal layer that are not connected by via hole connection and through hole connection (not shown).

[0204] (Roughening treatment and swelling treatment) The resin material is preferably used to obtain a cured product to be subjected to roughening treatment or desmear treatment. The cured product also includes a pre-cured product that can be further cured.

[0205] In order to form fine irregularities on the surface of the cured product obtained by pre-curing the resin material, the cured product is preferably subjected to a roughening treatment. The cured product is preferably subjected to a swelling treatment before the roughening treatment. The cured product is preferably subjected to a swelling treatment after the pre-curing and before the roughening treatment, and is further preferably cured after the roughening treatment. However, the cured product does not necessarily have to be subjected to a swelling treatment.

[0206] As a method of the swelling treatment, for example, a method of treating the cured product with an aqueous solution or an organic solvent dispersion solution of a compound mainly composed of ethylene glycol or the like is used. The swelling liquid used in the swelling treatment generally contains an alkali as a pH adjuster or the like. The swelling liquid preferably contains sodium hydroxide. Specifically, for example, the swelling treatment is performed by treating the cured product with a 40 wt% ethylene glycol aqueous solution or the like at a treatment temperature of 30 to 85°C for 1 to 30 minutes. The temperature of the swelling treatment is preferably within the range of 50 to 85°C. If the temperature of the swelling treatment is too low, the swelling treatment takes a long time, and the adhesive strength between the cured product and the metal layer tends to be lowered.

[0207] In the roughening treatment, a chemical oxidizing agent such as a manganese compound, a chromium compound, or a persulfate compound is used. These chemical oxidizing agents are used as an aqueous solution or an organic solvent dispersion after water or an organic solvent is added. The roughening solution used in the roughening treatment generally contains an alkali as a pH adjuster. The roughening solution preferably contains sodium hydroxide.

[0208] The manganese compounds include potassium permanganate and sodium permanganate. The chromium compounds include potassium dichromate and potassium chromate anhydride. The persulfate compounds include sodium persulfate, potassium persulfate, and ammonium persulfate.

[0209] The arithmetic mean roughness Ra of the surface of the cured product is preferably 10 nm or more, preferably less than 300 nm, more preferably less than 200 nm, and even more preferably less than 150 nm. In this case, the adhesive strength between the cured product and the metal layer is increased, and finer wiring is formed on the surface of the insulating layer. Furthermore, conductor loss can be suppressed, and signal loss can be suppressed. The arithmetic mean roughness Ra is measured in accordance with JIS B0601:1994.

[0210] (Desmear processing) Through holes may be formed in the cured product obtained by pre-curing the resin material. In the multilayer board, etc., vias or through holes are formed as the through holes. For example, vias can be formed by irradiating a laser such as a CO2 laser. The diameter of the via is not particularly limited, but is about 60 to 80 μm. Due to the formation of the through holes, smears, which are resin residues derived from the resin components contained in the cured product, are often formed at the bottom of the via.

[0211] In order to remove the smears, the surface of the cured product is preferably subjected to a desmear treatment. The desmear treatment may also serve as a roughening treatment.

[0212] In the desmear treatment, a chemical oxidizing agent such as a manganese compound, a chromium compound, or a persulfate compound is used, as in the roughening treatment. These chemical oxidizing agents are used as an aqueous solution or an organic solvent dispersion after water or an organic solvent is added. The desmear treatment liquid used in the desmear treatment generally contains an alkali. The desmear treatment liquid preferably contains sodium hydroxide.

[0213] By using the above resin material, the surface roughness of the surface of the cured product after the desmear treatment is sufficiently small.

[0214] The present invention will be specifically described below by way of examples and comparative examples, but the present invention is not limited to the following examples.

[0215] (Maleimide compounds having an aliphatic skeleton) N-alkylbismaleimide compound 1 ("BMI-1700" manufactured by Designer Molecules Inc., having a skeleton derived from dimer diamine, which is a reaction product of tetracarboxylic dianhydride and dimer diamine) N-alkylbismaleimide compound 2 ("BMI-3000" manufactured by Designer Molecules Inc., having a skeleton derived from dimer diamine, which is a reaction product of tetracarboxylic dianhydride and dimer diamine) N-alkylbismaleimide compound 3 (Designer Molecules Inc. "BMI-1500") N-alkylbismaleimide compound 4 (Designer Molecules Inc. "BMI-3000J") N-Alkylbismaleimide Compound 5 (synthesized according to Synthesis Example 1 below, has a skeleton derived from dimer diamine) N-alkylbismaleimide compound 6 (synthesized according to Synthesis Example 2 below, has a skeleton derived from dimer diamine)

[0216] (Synthesis Example 1) In a reaction vessel equipped with a stirrer, a water divider, a thermometer, and a nitrogen gas inlet tube, 135.0 g of tetracarboxylic dianhydride ("BisDA-1000" manufactured by SABIC Japan LLC) and 400 g of cyclohexanone were placed, and the solution in the reaction vessel was heated to 60°C. Then, 17.5 g of 1,3-bisaminomethylcyclohexane (manufactured by Mitsubishi Gas Chemical Co., Ltd.) was dropped into the reaction vessel and reacted to obtain a reaction product in which both ends are acid anhydrides. Then, 148 g of dimer diamine ("PRIAMINE1075" manufactured by Croda Japan Co., Ltd.) was slowly added to the reaction vessel, and then 60.0 g of methylcyclohexane was added to the reaction vessel. A Dean-Stark trap and a condenser were attached to the flask, and the mixture was heated to reflux for 2 hours to obtain an imide compound having an amine structure at both ends. Then, 28 g of maleic anhydride was added, and the resulting mixture was refluxed for another 12 hours. After the reaction was completed, isopropanol was added to cause reprecipitation, and the precipitate was then collected and dried to obtain an N-alkylbismaleimide compound having a skeleton derived from dimer diamine. The recovery rate of the N-alkylbismaleimide compound having a skeleton derived from dimer diamine was 83%. (Weight average molecular weight: 10,000)

[0217] (Synthesis Example 2) After stirring, 55 g of pyromellitic dianhydride (manufactured by Tokyo Chemical Industry Co., Ltd., molecular weight 254.15) and 300 g of cyclohexanone were placed in a reaction vessel equipped with a water divider, a thermometer, and a nitrogen gas inlet tube, and the solution in the reaction vessel was heated to 60°C. Next, a solution in which 26.7 g of bis(aminomethyl)norbornane (manufactured by Tokyo Chemical Industry Co., Ltd., molecular weight 154.26) was dissolved in cyclohexanone was dropped into the reaction vessel and reacted to obtain a reaction product in which both ends are acid anhydrides. Then, isopropanol was added, and an imide compound in which both ends are acid anhydrides was recovered. Next, the precipitate was dissolved again in cyclohexane, and 46.0 g of dimer diamine ("PRIAMINE1075" manufactured by Croda Japan Co., Ltd.) was slowly added to the reaction vessel, and then 45.0 g of methylcyclohexane was added to the reaction vessel. A Dean-Stark trap and a condenser were attached to the flask, and the mixture was heated to reflux for 2 hours to obtain an imide compound having an amine structure at both ends. The recovery rate of the maleimide compound was 70% (weight average molecular weight: 8700).

[0218] (Benzoxazine compounds having an aliphatic skeleton) N-alkylbisbenzoxazine compound (synthesized according to Synthesis Example 3 below)

[0219] (Synthesis Example 3) In a reaction vessel equipped with a stirrer, a water divider, a thermometer, and a nitrogen gas inlet tube, 65 g of pyromellitic dianhydride (manufactured by Tokyo Chemical Industry Co., Ltd., molecular weight 218.12) and 500 mL of cyclohexanone were placed, followed by dissolving 164 g of dimer diamine ("PRIAMINE 1075" manufactured by Croda Japan Co., Ltd.) in cyclohexanone and adding it dropwise. Then, a Dean-Stark trap and a condenser were attached to the flask, and the mixture was heated to reflux for 2 hours to obtain an imide compound having an amine structure at both ends. The obtained imide compound was mixed with 38 g of phenol (manufactured by Tokyo Chemical Industry Co., Ltd., molecular weight 94.11) and 12 g of paraformaldehyde (manufactured by Tokyo Chemical Industry Co., Ltd.), and the resulting mixture was refluxed for another 12 hours to perform benzoxazine conversion. Then, reprecipitation with isopropanol was performed to obtain an N-alkylbenzoxazine compound (weight average molecular weight 7700).

[0220] (Maleimide compounds not having an aliphatic skeleton (maleimide compounds having an aromatic skeleton)) N-phenylmaleimide compound 1 (manufactured by Daiwa Chemical Industry Co., Ltd., "BMI-2300") N-phenylmaleimide compound 2 ("BMI-4000" manufactured by Daiwa Chemical Industry Co., Ltd.)

[0221] (Polyimide Compounds) A solution containing a polyimide compound (non-volatile content: 26.8% by weight), which is a reaction product of tetracarboxylic dianhydride and dimer diamine, was synthesized according to Synthesis Example 4 below.

[0222] (Synthesis Example 4) In a reaction vessel equipped with a stirrer, a water divider, a thermometer, and a nitrogen gas inlet tube, 300.0 g of tetracarboxylic dianhydride ("BisDA-1000" manufactured by SABIC Japan LLC) and 665.5 g of cyclohexanone were placed, and the solution in the reaction vessel was heated to 60°C. Next, 89.0 g of dimer diamine ("PRIAMINE1075" manufactured by Croda Japan) and 54.7 g of 1,3-bisaminomethylcyclohexane (manufactured by Mitsubishi Gas Chemical Co., Ltd.) were dropped into the reaction vessel. Next, 121.0 g of methylcyclohexane and 423.5 g of ethylene glycol dimethyl ether were added to the reaction vessel, and the imidization reaction was carried out at 140°C for 10 hours. In this way, a polyimide compound-containing solution (non-volatile content 26.8% by weight) was obtained. The molecular weight (weight average molecular weight) of the obtained polyimide compound was 20,000. The molar ratio of acid component / amine component was 1.04.

[0223] The molecular weight of the polyimide compound synthesized in Synthesis Example 4 was determined as follows.

[0224] GPC (Gel Permeation Chromatography) Measurement: The measurements were performed using a Shimadzu high-performance liquid chromatograph system, with tetrahydrofuran (THF) as the developing medium, at a column temperature of 40°C and a flow rate of 1.0 ml / min. The detector used was an SPD-10A, and two Shodex KF-804L columns (with an exclusion limit of 400,000) were connected in series. Tosoh TSK Standard Polystyrene was used as the standard polystyrene, and a calibration curve was created using substances with weight-average molecular weights Mw = 354,000, 189,000, 98,900, 37,200, 17,100, 9,830, 5,870, 2,500, 1,050, and 500, and the molecular weights were calculated.

[0225] (thermoplastic resin) Phenoxy resin (Mitsubishi Chemical Corporation "YX6954BH30")

[0226] (thermosetting compound) Biphenyl-type epoxy compound ("NC-3000" manufactured by Nippon Kayaku Co., Ltd.) Naphthalene-type epoxy compound (DIC "HP-4032D") Resorcinol diglycidyl ether (Nagase Chemtex Corporation "EX-201") Dicyclopentadiene type epoxy compound (ADEKA Corporation "EP4088S") Naphthol aralkyl type epoxy compound ("ESN-475V" manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd.)

[0227] (Inorganic filler) Silica-containing slurry (75% silica by weight: Admatechs "SC4050-HOA", average particle size 1.0 μm, aminosilane treatment, cyclohexanone 25% by weight)

[0228] (hardening agent) Ingredient X: Cyanate ester compound-containing liquid ("BA-3000S" manufactured by Lonza Japan, solid content 75% by weight) Active ester compound 1-containing liquid (DIC Corporation "EXB-9416-70BK", solid content 70% by weight) Active ester compound 2-containing liquid (DIC Corporation "HPC-8000L", solid content 65% by weight) Liquid containing active ester compound 3 (DIC Corporation "HPC-8150", solid content 62% by weight) Liquid containing phenol compound (DIC Corporation "LA-1356", solid content 60% by weight) Carbodiimide compound-containing liquid (Nisshinbo Chemical's "V-03", solid content 50% by weight)

[0229] (Cure accelerator) Dimethylaminopyridine ("DMAP" manufactured by Wako Pure Chemical Industries, Ltd.) 2-Phenyl-4-methylimidazole ("2P4MZ" manufactured by Shikoku Chemical Industries, Ltd.) 2-Ethyl-4-methylimidazole ("2E4MZ" manufactured by Shikoku Chemical Industries, Ltd.) Dicumyl peroxide (Tokyo Chemical Industry Co., Ltd.)

[0230] (Example 1 to 13, Reference Example 14, Example 15, 16 and Comparative Examples 1 to 6) The components shown in Tables 1 and 2 below were mixed in the amounts shown in Tables 1 and 2 below, and stirred at room temperature until a homogeneous solution was obtained, to obtain a resin material.

[0231] Preparation of resin film: The obtained resin material was applied to the release-treated surface of a release-treated PET film (Toray Industries, Inc., "XG284", thickness 25 μm) using an applicator, and then dried for 2 minutes and 30 seconds in a gear oven at 100°C to volatilize the solvent. In this way, a laminated film (a laminated film of a PET film and a resin film) was obtained in which a resin film (B-stage film) with a thickness of 40 μm was laminated on the PET film.

[0232] (evaluation) (1) Handling The obtained resin film (B stage film) was folded 10 times by 180 degrees. The number of times that the resin film developed cracks or breaks was observed.

[0233] [Criteria for Handling] ○: Cracks or breaks occurred less than 3 times out of 10 times △: Cracks or breaks occurred 3 or more times but less than 6 times out of 10 times ×: Cracks or breaks occurred 6 or more times out of 10 times.

[0234] (2) Ability to embed into uneven surfaces and prevent overflow (prevention of excessive wetting and spreading) Only the copper foil of a 100 mm square copper-clad laminate (a laminate of a 400 μm thick glass epoxy board and a 25 μm thick copper foil) was etched to open dents (openings) with a diameter of 100 μm and a depth of 25 μm in a straight line across a 30 mm square area in the center of the board, with the distance between the centers of adjacent holes being 900 μm. In this way, an evaluation board with a total of 900 dents was prepared.

[0235] The resin film side of the obtained laminated film was placed on the evaluation substrate, and heated and pressed at a lamination pressure of 0.4 MPa for 20 seconds, a press pressure of 0.8 MPa for 20 seconds, and a lamination and press temperature of 90°C using a Meiki Seisakusho "Batch Type Vacuum Laminator MVLP-500-IIA." After cooling to room temperature, the PET film was peeled off. In this way, an evaluation sample in which a resin film was laminated on an evaluation substrate was obtained.

[0236] The obtained evaluation samples were observed for voids in the recesses using an optical microscope. The ratio of recesses in which voids were observed was evaluated to determine the embeddability of the sample against the uneven surface according to the following criteria.

[0237] [Criteria for embeddability on uneven surfaces] ○: The percentage of depressions where voids were observed was 0%. △: The percentage of depressions where voids were observed was greater than 0% and less than 5%. ×: The percentage of depressions in which voids were observed was 5% or more.

[0238] The obtained evaluation samples were observed using an optical microscope to see whether or not the resin film protruded from a predetermined area on the substrate, and the protrusion prevention property was judged according to the following criteria.

[0239] [Criteria for determining anti-extrusion performance] ○: The resin film protrudes less than 2 mm from the periphery of the evaluation board after lamination. △: The resin film protrudes from the periphery of the evaluation board after lamination more than 2 mm and less than 3 mm ×: The resin film protrudes from the periphery of the evaluation board after lamination by more than 3 mm.

[0240] (3) Curing temperature The exothermic peak associated with the curing of the obtained resin film (B-stage film) was evaluated using a differential scanning calorimeter (TA Instruments' "Q2000"). 8 mg of the resin film was placed in a special aluminum pan and covered with a special tool. This special aluminum pan and an empty aluminum pan (reference) were placed in a heating unit and heated in a nitrogen atmosphere from -30°C to 250°C at a heating rate of 3°C / min, and the reverse heat flow and non-reverse heat flow were observed. The curing temperature was confirmed from the exothermic peak observed in the non-reverse heat flow.

[0241] [Criteria for Curing Temperature] ○: All exothermic peaks are below 200℃ ×: At least one exothermic peak at a temperature higher than 200° C.

[0242] (4) Dielectric tangent The obtained resin film was cut into a size of 2 mm wide and 80 mm long, and five sheets were stacked together to obtain a laminate with a thickness of 200 μm. The obtained laminate was heated at 190° C. for 90 minutes to obtain a cured product. The dielectric tangent of the obtained cured product was measured at room temperature (23° C.) and a frequency of 1.0 GHz by the cavity resonance method using a "Cavity Resonance Perturbation Method Dielectric Constant Measurement Device CP521" manufactured by Kanto Electronics Application Development Co., Ltd. and a "Network Analyzer N5224A PNA" manufactured by Keysight Technologies, Inc.

[0243] [Criteria for dielectric tangent] ○: Dielectric tangent is 3.5×10-3 below ×: Dielectric tangent is 3.5×10 -3 Exceed

[0244] (5) Adhesion between the insulating layer and the metal layer (peel strength) Lamination process: A double-sided copper-clad laminate (copper foil thickness of 18 μm on each side, substrate thickness of 0.7 mm, substrate size 100 mm × 100 mm, Hitachi Chemical Co., Ltd. "MCL-E679FG") was prepared. Both sides of the copper foil surface of this double-sided copper-clad laminate were immersed in MEC Co., Ltd.'s "Cz8101" to roughen the copper foil surface. On both sides of the roughened copper-clad laminate, the resin film (B stage film) side of the laminate film was laminated on the copper-clad laminate using Meiki Seisakusho Co., Ltd.'s "Batch-type vacuum laminator MVLP-500-IIA" to obtain a laminated structure. The lamination conditions were reduced pressure for 30 seconds to an atmospheric pressure of 13 hPa or less, and then pressed at 100 ° C and a pressure of 0.4 MPa for 30 seconds.

[0245] Film peeling process: The PET films on both sides of the resulting laminated structure were peeled off.

[0246] Copper foil attachment process: The shiny side of the copper foil (thickness 35 μm, manufactured by Mitsui Kinzoku Co., Ltd.) was subjected to Cz treatment ("Cz8101" manufactured by MEC Co., Ltd.) and the copper foil surface was etched by about 1 μm. The etched copper foil was attached to the above-mentioned laminated structure from which the PET film had been peeled off to obtain a substrate with the copper foil. The obtained substrate with the copper foil was heat-treated at 190° C. for 90 minutes in a gear oven to obtain an evaluation sample.

[0247] Peel strength measurement: A 1 cm wide rectangular cut was made on the surface of the copper foil of the evaluation sample. The evaluation sample was set in a 90° peel tester (TE-3001, manufactured by Tester Sangyo Co., Ltd.), the end of the copper foil with the cut was picked up with a gripper, and the copper foil was peeled off by 20 mm to measure the peel strength.

[0248] [Criteria for determining adhesion (peel strength) between insulating layer and metal layer] ○○: Peel strength is 0.6kgf or more ○: Peel strength is 0.4kgf or more and less than 0.6kgf ×: Peel strength is less than 0.4 kgf

[0249] (6) Average coefficient of linear expansion (CTE) The resulting 40μm thick resin film (B-stage film) was heated at 190℃ for 90 minutes, and the resulting cured product was cut into pieces measuring 3mm x 25mm. Using a thermomechanical analyzer (SII NanoTechnology's "EXSTAR TMA / SS6100"), the average linear expansion coefficient (ppm / ℃) of the cut cured product from 25℃ to 150℃ was calculated under conditions of a tensile load of 33mN and a heating rate of 5℃ / min.

[0250] [Criteria for determining average linear expansion coefficient] ○: Average linear expansion coefficient is 25 ppm / ℃ or less △: Average linear expansion coefficient is more than 25 ppm / ℃ and less than 30 ppm / ℃ ×: Average linear expansion coefficient exceeds 30 ppm / ℃

[0251] (7) Bending stability of the cured product The resulting 40 μm thick resin film (B-stage film) was heated at 190° C. for 90 minutes, and the resulting cured product was cut into a size of 30 mm x 150 mm. A downward bending test was performed using a planar U-shaped folding tester (manufactured by Yuasa Corporation) under the conditions of 200 times / min, 180° folding (bending gap 5 mm), and film stroke 70 mm. The measurement was repeated five times, and the average value was calculated.

[0252] [Criteria for determining bending stability of cured products] 〇〇: No cracks after 2000 folds 〇: Cracks occurred after bending 100 to 2000 times ×: Cracks occurred after bending less than 100 times

[0253] The compositions and results are shown in the following Tables 1 and 2. In Table 1, the content of each component is shown as the pure amount.

[0254] [Table 1]

[0255] [Table 2] [Explanation of symbols]

[0256] 11...Multilayer printed wiring board 12...Circuit board 12a…Top surface 13~16…Insulating layer 17...Metal layer

Claims

1. A polyimide compound, An aliphatic skeleton-containing compound; and an inorganic filler, The weight average molecular weight of the polyimide compound is 15,000 or more, The weight average molecular weight of the aliphatic skeleton-containing compound is less than 15,000, the aliphatic skeleton-containing compound is a maleimide compound having an aliphatic skeleton, the aliphatic skeleton-containing compound has a skeleton derived from a reaction product of a polyamine compound having an aliphatic skeleton and a carboxylic dianhydride, a total content of the polyimide compound and the aliphatic skeleton-containing compound is 10% by weight or more and 80% by weight or less based on 100% by weight of organic components excluding a solvent in a resin material; A resin material, in which the content of the inorganic filler is 50% by weight or more based on 100% by weight of components excluding the solvent in the resin material.

2. The resin material according to claim 1 , wherein in the aliphatic skeleton-containing compound, the aliphatic skeleton is bonded to a nitrogen atom forming a maleimide skeleton.

3. The resin material according to claim 1 or 2, wherein the aliphatic skeleton-containing compound has a skeleton derived from a reaction product of a diamine compound having an aliphatic skeleton and a carboxylic acid dianhydride.

4. The resin material according to claim 3 , wherein the diamine compound having an aliphatic skeleton is a diamine compound having a skeleton derived from dimer diamine.

5. The resin material according to any one of claims 1 to 4, comprising a thermosetting compound.

6. The resin material according to claim 5 , wherein the thermosetting compound is an epoxy compound.

7. 7. The resin material according to claim 1, wherein a content of the polyimide compound is 3% by weight or more and 80% by weight or less in a total of 100% by weight of the polyimide compound and the aliphatic skeleton-containing compound.

8. The resin material according to any one of claims 1 to 7, wherein the polyimide compound is a polyimide compound having a skeleton derived from a dimer diamine.

9. Contains a curing accelerator, The resin material according to any one of claims 1 to 8, wherein the curing accelerator comprises at least one of a radical curing accelerator and an anionic curing accelerator.

10. Contains a curing agent and a curing accelerator, The resin material according to any one of claims 1 to 8, wherein the curing accelerator comprises an imidazole compound.

11. The resin material according to any one of claims 1 to 10, which is a resin film.

12. The resin material according to any one of claims 1 to 11, which is used to form an insulating layer in a multilayer printed wiring board.

13. A substrate; A resin film laminated on a surface of the substrate, The resin film is a laminated film made of the resin material according to any one of claims 1 to 12.

14. A circuit board; a plurality of insulating layers disposed on a surface of the circuit board; a metal layer disposed between a plurality of the insulating layers; A multilayer printed wiring board, wherein at least one of the insulating layers is a cured product of the resin material according to any one of claims 1 to 12.

Citation Information

Patent Citations

  • Thermosetting polyimide resin composition and molded product and electronic part using the same

    JP2007119507A

  • Particle-reinforced fiber-reinforced polymer composite materials

    JP2012528236A

  • Polyimide-based adhesive composition, cured product, adhesive sheet, laminate, and flexible printed board

    JP2013199645A

  • Resin composition

    JP2015145498A

  • Copper foil with resin, copper-clad laminate, printed wiring board and multilayer wiring board

    JP2017119361A